TRANSFORMATIONAL-DISTRIBUTIVE METHOD IN STUDYING THE SEMANTICS OF THREE-ACTANT VERBS (Web of Teachers: Inderscience Research, 2024)
The article considers the transformational-distributive method of studying semantic classes of transitive verbs in a comparative aspect using the material of the Russian and Uzbek languages. The study of semantic classes of transitive verbs, identified on the basis of valence differences, allows using the mechanism of encoding predicative phrases for the purposes of teaching the Russian language.